Transforming cross‐cultural water research through trust, participation and place. (13th August 2015) - Woodward, Emma; Marrfurra McTaggart, Patricia
Abstract: Indigenous voices in government‐led natural resource management planning processes are often marginalised, misinterpreted, or excluded. Third parties, including government‐employed geographers, can act as knowledge brokers in defining Indigenous values and interests so they might be included in government planning processes. This paper reviews and assesses a research partnership that evolved to document the complex and diverse ecological and hydrological values held by Ngan'gi speakers about the Daly River and connected water places in the Northern Territory, Australia. The development of trust through the slow building of a relationship based on place‐based dialogue, a key aspect of participatory action research (PAR), created the foundation from which a mutually beneficial and respectful research partnership was able to, and continues to, evolve. Both research partners' perspectives are revealed here to articulate why the research partnership was deemed a success. Key lessons learned from the research partnership include the importance of trust, respect for place‐based learning, researcher and institutional flexibility, and awareness of the intricacies of relationship building and the benefits that research engagement can bring to Indigenous people and communities. We aim to further dialogue among geographers and interested disciplines as to the potential for PAR methods to foster mutually beneficial Indigenous–non‐Indigenous research partnerships.